Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
d)
[tex](2 \frac{3}{4}-3,5)*(-2^2)=(\frac{11}{4}-\frac{35}{10})*(-4)=(\frac{110}{40}-\frac{140}{40})*(-4)=(-\frac{30}{40})*(-4)=\frac{30}{10}=3[/tex]
f)
[tex](0,75-(-\frac{3}{4})^2)^2=(\frac{3}{4}-\frac{9}{16})^2=(\frac{12}{16}-\frac{9}{16})^2=(\frac{3}{16})^2=\frac{9}{256}[/tex]
4 c)
[tex]x=-48:0,6+1 \frac{2}{3}*54-1 \frac{5}{7}: 1 \frac{1}{14}=-48:\frac{6}{10}+\frac{5}{3}*54- \frac{12}{7}:\frac{15}{14}=-48*\frac{10}{6}+5*18-\frac{12}{7}*\frac{14}{15}=-80+90-\frac{4*2}{5}=10-\frac{8}{5}=\frac{50-8}{5}=\frac{42}{5}[/tex]
zatem liczba przeciwna do x to [tex]-\frac{42}{5}[/tex]
[tex]y=1 \frac{1}{3}*(-3 \frac{3}{5})+(\frac{3}{5}-2 \frac{4}{15})*0,5=\frac{4}{3}*(-\frac{18}{5})+(\frac{3}{5}-\frac{34}{15})*\frac{1}{2}=-\frac{4*6}{5}+(\frac{9-34}{15})*\frac{1}{2}=-\frac{24}{5}-\frac{25}{15}*\frac{1}{2}=-\frac{24}{5}-\frac{5}{3}*\frac{1}{2}=-\frac{24}{5}-\frac{5}{6}=-\frac{144}{30}-\frac{25}{30}=-\frac{169}{30}[/tex]
Zatem liczba odwrotna do y to [tex]-\frac{30}{169}[/tex]
Odpowiedź:
zad 10 d)
[tex](2\frac{3}{4}-3,5)*(-2^{2})=(\frac{11}{4}-\frac{7}{2})*4=(\frac{11}{4}-\frac{14}{4})*4=(-\frac{3}{4})*4=-\frac{12}{4}=-3[/tex]
zad 10 f)
(0,75-(-³/₄)²)²=[tex](\frac{3}{4}-(-\frac{3}{4})^{2})^{2}=(\frac{3}{4}-\frac{9}{16})^{2}=(\frac{12}{16}-\frac{9}{16})^{2} =[/tex][tex](\frac{3}{16})^{2}=\frac{9}{256}[/tex]
zad 4 c)
x=-48:0,6+1²/₃*54-1⁵/₇:1¹/₁₄=
-80+⁵/₃*54-¹²/₇:¹⁵/₁₄=
-80+²⁷⁰/₃-¹²/₇*¹⁴/₁₅=
-80+90-¹⁶⁸/₁₀₅=-80+90-1,6=10-1,6=8,4
y=[tex]1\frac{1}{3}*(-3\frac{3}{5})+(\frac{3}{5}-2\frac{4}{15})*0,5=[/tex]
[tex]\frac{4}{3}*(-\frac{18}{5})+(\frac{9}{15}-\frac{34}{15})*0,5=[/tex]
[tex]-\frac{24}{5}+(-\frac{25}{15})*\frac{1}{2}=[/tex]
[tex]-\frac{24}{5}+(-\frac{25}{30})=[/tex]
[tex]-\frac{144}{30}-\frac{25}{30}=[/tex][tex]-\frac{169}{30}[/tex]=
[tex]-5\frac{19}{30}=-5,63[/tex]
Szczegółowe wyjaśnienie: